2016
DOI: 10.1177/1098611116667279
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Limits of Technology’s Impact on Police Effectiveness

Abstract: Technology has become a major source of expenditure and innovation in law enforcement and is assumed to hold great potential for enhancing police work. But does technology achieve these expectations? The current state of research on technology in policing is unclear about the links between technologies and outcomes such as work efficiencies, effectiveness in crime control, or improved police-community relationships. In this article, we present findings from a mixed-methods, multiagency study that examines fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
60
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 86 publications
(66 citation statements)
references
References 49 publications
1
60
0
5
Order By: Relevance
“…A final area of research that has been the least examined is the impact that BWCs have on police organizations. In studies on police technologies, scholars have found that technologies often have unintended consequences on police organizations and may not deliver on their expectations (Chan et al., ; Koper et al., ; Lum et al., ; Manning, ). For example, proponents of BWCs have high expectations of them for police organizations, believing that they can improve training, tighten accountability structures and disciplinary systems and practices, or sharpen supervisory practices.…”
Section: Body‐worn Cameras and Police Organizationsmentioning
confidence: 99%
See 1 more Smart Citation
“…A final area of research that has been the least examined is the impact that BWCs have on police organizations. In studies on police technologies, scholars have found that technologies often have unintended consequences on police organizations and may not deliver on their expectations (Chan et al., ; Koper et al., ; Lum et al., ; Manning, ). For example, proponents of BWCs have high expectations of them for police organizations, believing that they can improve training, tighten accountability structures and disciplinary systems and practices, or sharpen supervisory practices.…”
Section: Body‐worn Cameras and Police Organizationsmentioning
confidence: 99%
“…Perhaps more important to point out is that technologies often do not reform organizations insomuch as organizations shape (or inhibit) the use of the technology (Lum et al., ; Manning, ). Both citizens and police leaders might expect BWCs to strengthen the accountability infrastructure in policing (i.e., procedures for complaints and discipline; supervision, mentorship, and oversight; or recording and accounting of actions).…”
Section: Body‐worn Cameras and Police Organizationsmentioning
confidence: 99%
“…The science behind criminal justice programs and interventions is much more robust than the evidence base of criminal justice technologies. Especially in policing, we still do not know whether both older technologies such as computer‐aided dispatch, forensics, or information technologies, or newer technologies such as body‐worn cameras, predictive analytics, or license‐plate readers, create measurable crime prevention and control improvements and whether those outweigh their unintended consequences (Lum, Koper, and Willis, ). And, as discussed by Paul Wormeli (, this issue), there remains much more potential to use the data from information technologies to improve understanding and evaluate police activities and citizen reactions to those activities.…”
Section: Developments During the Past 50 Yearsmentioning
confidence: 99%
“…Until recently, however, there has been little research on the value premise of all of the new technology that has been unleashed in law enforcement and the administration of justice, with a goal of determining how the technology explosion has been instrumental in improving performance of either law enforcement or the administration of justice. In the available research, scholars have generally challenged the implicit assumption that the application of the many new technologies will somehow improve the performance of law enforcement agencies, finding that the inhibitions of cultural norms may be more influential in determining how the use of advanced technologies results in performance improvements (Koper, Lum, and Willis, ; Lum, Koper, and Willis, ).…”
Section: The Changing Environmentmentioning
confidence: 99%